Prevalence and determinants of mother and newborn skin-to-skin contact: an assessment from the 2017-18 BDHS data - Azaz Bin Sharif; Mohammad Delwer Hossain Hawlader; Mohammad Hayatun Nabi (BMC Pregnancy and Childbirth, 2025)
Abstract Background Evidence shows that skin-to-skin contact (SSC) enhances children’s well-being. More information is needed on the prevalence and determinants of SSC in Bangladesh. This study aimed to estimate the prevalence and associated factors of mothers and their newborns’ skin-to-skin contact in Bangladesh. Methods Data extracted from a cross-sectional survey, (Bangladesh Demographic and Health Survey (BDHS) 2017-18), where 5304 (unweighted) women who gave birth in the last 3 years preceding the survey were included in the final analysis. Multivariable logistic regression analysis was used to identify the determinants of SSC practice. Adjusted odds ratios (aORs) with their corresponding 95% confidence intervals (CIs) were reported. Results The prevalence of SSC practice in Bangladesh was 15.6% (95% CI [14.3, 17.0]). The adjusted regression model showed that the SSC practice was significantly associated with the geographic region, place of delivery, mode of delivery, and number of antenatal care visits. The SSC practice was 50% lower (aOR = 0.5, 95% CI [0.3, 0.8]) in the Rajshahi Division compared to the Dhaka Division. Women who had an institutional delivery had 2 times higher odds (aOR = 2.0, 95% CI [1.6, 2.5]) of SSC practice than women who had experienced a non-institutional delivery. Compared to women who delivered by cesarean section, the odds of SSC practice were 2.1 times higher (aOR = 2.1, 95% CI [1.6, 2.6]) for women who had a normal delivery. Women who completed at least four antenatal visits had 20% higher odds (aOR = 1.2, 95% CI [1.0, 1.4]) of SSC practice than women who completed fewer than four antenatal visits. Conclusion Given that only approximately one-sixth of the surveyed women are engaged in SSC practice, informal instructional and awareness programs are necessary in Bangladesh to promote the importance and extent of SSC practice.